Estimación del área foliar a partir de la superficie de albura en Pinus sylvestris - Barrantes O.; Gracia C.A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
In this paper, one application of the Waring's method to estimate leaf area index, in Pinus sylvestris, is presented. Cross-sectional sapwood area was measured at different heights in four trees and was related to the leaf area sustained over each stem point. A satisfactory correlation between both variables was found, the coefficient of determination being 0.9 and the relationship between leaf area (m2) and sapwood area (cm2) was 0.18. A way to estimate leaf area index of the forest is presented and a few aspects related with functional and structural problems of Pinus sylvestris are discussed.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)